Theoretical Study of Sensitivity of Slab-Sensor with Metamaterial - Yasser, Hassan A.; Shaddod, Sarah A. (University of Thi-Qar Journal, 2019)
In this paper, a plane waveguide consisting of three layers was studied, where the metamaterial was placed in the middle region. The dispersion relation equations, field distribution, power flux, and sensitivity were derived, by Maxwell’s equations. The results showed that the waveguide contains only the transverse modes TE and TM, while the fundamental mode is absent compared of normal materials. The study of dispersion curves showed that all modes contain a backward orientation in a certain range of V. This amount of backward orientation decreases with increasing the mode order. Also the study showed that the sensitivity increases by increasing the middle width of waveguide or mode order.